Effect of Plasma-Activated Water Combined with Biological Preservatives on Beef Preservation - KE Zhigang, TIAN Yuling, LIU Shulai, ZHOU Xuxia, DING Yuting (Shipin Kexue)
To prolong the shelf life of fresh beef, we designed and evaluated a preservative (PAW-ε-PLH-nisin) by dissolving ε-polylysine hydrochloride (ε-PLH), nisin, and sodium hexametaphosphate as a water-retaining agent in plasma-activated water (PAW). The effect of the preservative on the quality changes of beef during cold storage was investigated. The results demonstrated that after storage under vacuum at 4 ℃ for 28 days, the total bacterial count of beef treated with the preservative was 5.1 (lg(CFU/g)), within the acceptable limit. The total volatile basic nitrogen (TVB-N) content was 18.3 mg/100 g after 21 days of storage, meeting the criteria for the second freshness grade. The PAW-ε-PLH-nisin treatment notably improved the redness of beef, kept beef texture and sensory characteristics stable during storage, delayed lipid and protein oxidation in beef, and maintained fatty acid stability. These results suggest that PAW-ε-PLH-nisin has significant application potential and high development value in fresh beef preservation.